(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Constitution of India is actually federal in type but is a lot more unitary in character. To strengthen the federal system is actually needed for meeting the aspirations of the individuals who are actually governed by State Governments and for protecting the unity of India. Thus, center-state relations, i.e. the arrangements between the Union Government and also the States in regard to the powers of theirs, duties and functions, have usually been an important concern. In a method of multi-level governance, operating basically in federal framework, that way of India, harmonious relations between the States and also the Centre are actually crucial for the stability, economic development and security of the nation. Additionally, it tries to bring to light some other critical shortcomings of the current setup of center-state monetary relations.